2009
DOI: 10.1002/fam.1000
|View full text |Cite
|
Sign up to set email alerts
|

The use of fire‐retardant intumescent mats for fire and heat protection of glass fibre‐reinforced polyester composites: Thermal barrier properties

Abstract: SUMMARYThis study investigates the use of integral, hybrid intumescent thermal barriers (mats) to provide surface protection to the core fibre-reinforced polyester composite structural integrity when exposed to a fire or heat source. Glass fibre-reinforced composites protected by intumescent mats/fabrics containing silicate fibres, expandable graphite and in some cases borosilicate glass bounded together by an organic matrix have been evaluated for fire performance under a constant heat flux of 50 kW/m 2 . The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 19 publications
0
28
0
1
Order By: Relevance
“…The fire performance of surface-insulated and fire-retarded composites is superior to that of the control composite (P) or the composites that contain additives alone. The use of insulative fabrics purely as surface barriers (with no infused resin) produced better fire resistance for GRP core composites than observed otherwise in our previous work published elsewhere when the surface layer was infused with resin in order to have a consolidated structural composite [12].…”
Section: Percent Reduction In Thr (%)mentioning
confidence: 81%
See 3 more Smart Citations
“…The fire performance of surface-insulated and fire-retarded composites is superior to that of the control composite (P) or the composites that contain additives alone. The use of insulative fabrics purely as surface barriers (with no infused resin) produced better fire resistance for GRP core composites than observed otherwise in our previous work published elsewhere when the surface layer was infused with resin in order to have a consolidated structural composite [12].…”
Section: Percent Reduction In Thr (%)mentioning
confidence: 81%
“…Previous work in our laboratories has shown that the use of fire retardants in resin formulations leads to the formation of residual char network following the decomposition of the resin matrix [1,4,5,14,15]. Recently, we have shown success in the use of insulative fabrics to improve the fire performance of polyesterbased composites [12]. The effect of fire-retardant additives and the insulative fabric on the mechanical property retention after heat exposure has been studied herein.…”
Section: Flexural Performance After Exposure To Radiant Heatmentioning
confidence: 94%
See 2 more Smart Citations
“…The use of integral, hybrid intumescent thermal barriers to provide surface protection to the core fiber-reinforced polyester composite structural integrity when exposed to a fire or heat source was also investigated [19]. Glass fiber-reinforced composites protected by intumescent mats/fabrics containing silicate fibers, expandable graphite and in some cases borosilicate glass bounded together by an organic matrix have been evaluated for fire performance under a constant heat flux of 50 kW/m 2 .…”
mentioning
confidence: 99%